2011
DOI: 10.1111/j.1542-4758.2011.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying home medication regimen changes and quality of life in patients receiving nocturnal home hemodialysis

Abstract: Medication regimen simplification may improve adherence in end-stage kidney disease. The effect of nocturnal home hemodialysis (NHHD) on medication burden is unknown. A retrospective pilot study of NHHD patients was conducted. Medication information was collected at baseline, NHHD start, and at 3, 6, 12, 18, and 24 months. SF-36 scores were collected at baseline, 6, 12, and 24 months. The number of medications, pill burden, and number of administrations per day were determined. Medication Regimen Complexity In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 28 publications
3
34
0
1
Order By: Relevance
“…The mean MRCI score in this study was comparable to that reported in home hemodialysis patients [13] , though expectedly much higher than the previous studies in non-ESKD (mean MRCI 15.5) [22] and institutionalized elderly people (mean MRCI 18.2) [23] . Our results of low rates of medication adherence among hemodialysis patients corroborated earlier findings [6,12,24] .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The mean MRCI score in this study was comparable to that reported in home hemodialysis patients [13] , though expectedly much higher than the previous studies in non-ESKD (mean MRCI 15.5) [22] and institutionalized elderly people (mean MRCI 18.2) [23] . Our results of low rates of medication adherence among hemodialysis patients corroborated earlier findings [6,12,24] .…”
Section: Discussionsupporting
confidence: 59%
“…However, only a small number of studies have assessed regimen complexity using the MRCI tool in chronic illnesses, including ESKD [9] . A significant increase in MRCI scores was observed over time when patients were switched from hospitalbased to home-based hemodialysis modality [13] . To the best of our knowledge, studies exploring regimen complexity as a likely determinant of medication adherence in hemodialysis patients are lacking.…”
Section: Introductionmentioning
confidence: 94%
“…Data for other populations of dialysis patients are relatively sparse. In a prospective, observational study of 42 patients undergoing peritoneal dialysis, the mean number of prescription medications was 9.2, and the mean number of nonprescription A single center study of 35 patients suggested that transitioning patients from in-center to nocturnal home hemodialysis may not result in a significant change in the number of medications (10.5 versus 11.8, P$0.05) (4). Although the use of antihypertensives and drugs for mineral and bone metabolism decreased, pill burden from vitamins and antiinfective medications increased.…”
Section: The Burden Of Mrps In Dialysis Patients Is Highmentioning
confidence: 99%
“…Several surveys of dialysis patients in the United States indicate that they are prescribed an average of 11-12 medications per day and take, on average, 17-25 doses per day (1)(2)(3)(4). This substantial medication burden comes at a considerable societal cost, because 61%-73% of Medicareenrolled dialysis patients obtain prescription drug coverage through Medicare Part D; also, parenteral medications administered in a dialysis facility for these patients are paid through Medicare Part B.…”
Section: Introductionmentioning
confidence: 99%
“…29 In earlier studies, correlation between medication complexity and health-related QoL has been a controversial subject. While Cardone et al (2011) did not find a significant relationship between the medication regimen complexity and SF-36 in the setting of nocturnal home dialysis patients, 55 a higher pill burden was associated with lower QoL for patients with traditional in-center hemo-dialysis. 56 Our study aimed at increasing adherence by reducing the complexity of medication regimens and indirectly influencing QoL.…”
Section: ■■ Discussionmentioning
confidence: 97%